In defence of Just War - Biggar, N (Faculty of Theology, University of Ljubljana, 2014)
What I write below about just war thinking will operate primarily in terms of the Christian tradition. Why? Will this not limit the appeal of what I have to say, attracting only the interest of Christians and excluding others? Why do I not I talk about just war in secular terms, which are universally intelligible and accessible? Why must I be religious, confessional, sectarian?